Paciente de sexo masculino de 20 años de edad diagnosticado con gastritis crónica - Santana Vera, María Belén (2020)
The present case study is about a 20-year-old with a weight of 48 kg and a size of 165 cm male patient who attended a medical consultation due to abdominal pain, weight loss, more vomiting due to many repetitions and loss of appetite, and a moderate alcohol consumer. Patient comes accompanied by his parents and they report that the patient has been a consumer of illicit substances since he was 16 years old, which is why they decided to confine him to a drug addiction rehabilitation clinic 4 months ago, for a year he has suffered from gastritis, but an approximately month begins with burning abdominal pain located in the epigastrium with increase to moderate intensity and that was accompanied in the last days with vomiting once a day the patient reported that he ate little and did not eat even for days, which caused loss of weight more quickly, the doctor performs endoscopy plus biopsy where he reflects erythema of the gastric mucosa, pale mucosa with visualization of submucosal vessels and thickening of the folds and is diagnosed with chronic gastritis. The nutritional evaluation is carried out with anthropometric, biochemical, clinical and dietary indicators, where the patient is diagnosed with moderate malnutrition related to a deficient intake of food and nutrients evidenced by data of the body mass index of 17, 64kg / m2 and hypocaloric feeding, hypo protein, hypo fat and low carbohydrates according to the 24-hour reminder, the objective of this case is to intervene nutritionally in the patient and a diet of 1900kcal soft gastric hyperprotein fractionated in 5 meal times is prescribed, soft consistency, moderate volume, temperature temperate and low fiber, where positive results are observed through follow-up, where there is a significant weight gain and favorable effects of the diet before the disease.